2022
DOI: 10.1080/23802359.2021.2018952
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of a tropical midge Chironomus kiiensis Tokunaga, 1936 (Diptera: Chironomidae)

Abstract: In this study, we presented the complete mitochondrial genome of a tropical midge Chironomus kiiensis Tokunaga by Illumina sequencing technology. The complete mitogenome of C. kiiensis is 15,710 bp in length, including 13 protein-coding genes (PCGs), two ribosomal RNAs and 22 tRNAs. The overall nucleotide composition is A: 39.3%, T: 37.6%, C: 13.6%, and G: 9.5%. Most PCGs use ATN as the start codon excluding COX1 (TTG), and most PCGs use TAA as the stop codon exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…AT-skew analysis reveals T-biased PCGs and rRNAs, while tRNAs exhibited an A-biased pattern (Table 2). As expected, M. umbrosus shares similar mitogenomic features with other Chironomidae species, such as Chironomus kiiensis Tokunaga, 1936 and Polypedilum unifascium Tokunaga, 1938 (Lei et al 2021, Liu et al 2022). Chironomidae mitogenomes present stability, maintaining similar gene content, gene arrangement, and base composition.…”
Section: Resultssupporting
confidence: 78%
“…AT-skew analysis reveals T-biased PCGs and rRNAs, while tRNAs exhibited an A-biased pattern (Table 2). As expected, M. umbrosus shares similar mitogenomic features with other Chironomidae species, such as Chironomus kiiensis Tokunaga, 1936 and Polypedilum unifascium Tokunaga, 1938 (Lei et al 2021, Liu et al 2022). Chironomidae mitogenomes present stability, maintaining similar gene content, gene arrangement, and base composition.…”
Section: Resultssupporting
confidence: 78%
“…Hence, phylogenetics among Chironomus has never been tested based on mitogenomes. Prior to this study, the mitogenomes of three Chironomus species have been reported [19][20][21], and the comparative analysis of nucleotide composition and evolutionary rates within the genus have never been carried out.…”
Section: Introductionmentioning
confidence: 99%
“… 2022 ), MZ150770 (Liu et al. 2022 ), MZ261913 (Kong et al. 2021 ), MZ981735 (this study), MW677959 (Lei et al.…”
Section: Resultsmentioning
confidence: 51%